Elaboración del diagnóstico del grado de madurez en gestión de portafolio de las organizaciones del grupo de interés de PMO de Bogotá, Colombia (2018)
Although projects are the fundamental basis of a solid organizational strategy, project management is not yet recognized as a necessary and relevant process, making it difficult to align the organizational strategy with the proper management of projects, programs and portfolios. This problem shows that the lack of an organizational culture in terms of maturity for project management, negatively impacts business competitiveness. Therefore, this research article exposes the process of diagnosis of the degree of maturity in portfolio management of the organizations of the PMO interest group in Bogotá, answering the question: What is the degree of maturity in the management of portfolios of the organizations in Colombia and how can they reach a higher level starting from their current condition? To do this, we propose the Maturity Model in Portfolio Management MMGPf, which is based on both research work and contributions from various experts and is implemented in these organizations. Thus, the scope of the research is of a qualitative exploratory nature, with a research - action type design, from which it will be found that none of the organizations studied has a defined and documented portfolio performance plan where they are established. the policies and procedures to define the value of the portfolio.